The role of the urban system in a regional government's location policy - Toshiharu Ishikawa (European Regional Science Association (ERSA), 2012)
Regional governments carry out a series of plans to attract firms to the area to stimulate the economic activity. The firms which are enticed to locate at the area are selected according to the characteristics of the regional economy. These firms are expected to operate the production processes in harmony with the regionfs characteristics and develop sustainably the regionfs economy. While the firms that plan to build a new factory select a region in a large geographical area for the new establishment to maximize profits. They compare the regionsf characteristics in terms of their own interests and determine the region for the factory. It is important for both regional governments and firms to understand the social and economic characteristics of regions and their comparative advantages. Present paper, first, examines the process of the location decision-making of a firm in these days in which economic globalization is common. It is theoretically elucidated in this examination why the characteristics of regional economy play an important role in a firmfs decision-making on the location of a factory. And then, using the empirical analysis of the relationships between Japanese regional economies and urban systems laid in the regions, the paper shows that the structure of urban system influences the regionfs social and economic performances. It is concluded from the analysis that the urban systems laid on the regions should be paid more attention by both regional governments and firms because the urban system is related with social and economic achievements in a region and it influences the profit level of the firms and the regionfs power to attract firms to the area.
Keywords: R30; 330; Urban system; Firm's location; Social health; Chaotic phenomenon Second best location; Prospective area